Theoretical Study of Improving Radiotherapy at High Energies (2-15) MeV for Lung Cancer using Nanocomposites - Sarhan, Walaa S.; Shiltagh, Nagham M. (Iraqi Journal of Science, 2025)
In this research shows how radiation therapy can be improved and developed using different structures of glucose molecules (α‐D glucose) C6H12O6 and C12H24O12 after adsorption on silver nanoparticles-AgNPs surface. This is by enhancing the radiation sensitivity (SER) of cancer cells in the human lung and meanwhile preserving the healthy cells surrounding the tumour itself. The primary role of AgNPs is as radiosensitizers that work to increase the absorbed dose of radiation in the presence of nanocomposites. Using a mathematical model to calculate the number of cancer cells remaining when exposed to radiation doses, where radiation sensitivity of C6H12O6Ag3 and C12H24O12Ag compounds were calculated theoretically. It was found that the C6H12O6Ag3 compound SER increases upon an increase in the absorbed dose of radiation. It equals 15.6 at the maximum energy value of (15MeV). Increasing radiation sensitivity values is accompanied by a decrease in the number of radiotherapy sessions by half. This is considered a noticeable improvement in radiotherapy. However, with the C12H24O12Ag configuration, SER values were found to be 12.9 at the maximum energy value. This value corresponds to a decrease in the number of radiotherapy sessions. Consequently, the C6H12O6Ag3 molecule structure could be the best radiosensitizer in cancer treatment.